Chemoselective and Metal-Free Synthesis of Aryl Esters from the Corresponding Benzylic Alcohols in Aqueous Medium Using TBHP/TBAI as an Efficient Catalytic System - Nandy, Sneha; Ghatak, Avishek; Das, Asit Kumar; Bhar, Sanjay (Synlett, 2018)
A novel and transition-metal-free strategy has been developed for the synthesis of aryl esters starting from corresponding benzylic primary alcohols as the exclusive substrates using tert-butyl hydroperoxide (TBHP) as a terminal oxidant in the presence of catalytic amount of tetrabutylammonium iodide (TBAI) and imidazole, where the aliphatic alcohols remained unaffected. These reactions are highly chemoselective and associated with high yield and wide applicability accommodating a wide range of substituents. Excellent chemoselectivity has also been demonstrated through intramolecular competition experiments. This protocol can be considered as an important analogue of Tishchenko reaction using benzylic alcohols as the substrates instead of benzaldehydes.
Keywords: aqueous reaction; chemoselectivity; green chemistry; esters; oxidation